2020
DOI: 10.3389/fonc.2020.522015
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Infiltrating Lymphocyte-Based Risk Score for Predicting Prognosis in Gastric Cancer

Abstract: Tumor-infiltrating lymphocytes (TILs) in gastric cancer are closely related to clinical prognosis; however, little is known regarding the immune microenvironment in this disease. Thus, RNA-sequencing data from gastric cancer patients were downloaded from the Gene Expression Omnibus (GEO). The proportion of immune cells was determined based on a deconvolution algorithm (CIBERSORT), and gene expression profiles were analyzed in the context of clinical outcomes to construct an immune risk score. Data were analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Many studies have reported the positive association of high TILs level with survival of multiple tumors, like breast cancer (BC) [ 33 ] or non-small-cell lung cancer (NSCLC) [ 34 ], which improves the curative effect of neoadjuvant chemotherapy in breast cancer [ 35 ]. In addition, TILs are known as predictive prognostic markers for gastric cancer [ 36 , 37 ]. However, some studies have shown that TILs exhibit no correlation with gastric cancer prognosis [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported the positive association of high TILs level with survival of multiple tumors, like breast cancer (BC) [ 33 ] or non-small-cell lung cancer (NSCLC) [ 34 ], which improves the curative effect of neoadjuvant chemotherapy in breast cancer [ 35 ]. In addition, TILs are known as predictive prognostic markers for gastric cancer [ 36 , 37 ]. However, some studies have shown that TILs exhibit no correlation with gastric cancer prognosis [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In subsequent work, we will collect information from GC patients who have undergone immunotherapy to further explore the influence of the TIIC score on therapeutic benefits. Many solid tumors are associated with immune cell infiltration in the tumor immune microenvironment, which affects therapy efficacy and overall survival to no small extent, yet the predictive role of individual cells on tumor prognosis is limited ( 38 , 39 ). It is hypothesized that the integration of multiple immune cells may improve the prediction of prognosis for GC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Memory B cells, plasma cells and NK activated cells all have a downward trend, although not all of them have significant statistical differences. In gastric cancer, 28 the activated CD4 + memory T cells and plasma cells, 29 contrary to resting CD4 + memory T cells, has been known as a protective factor. And for macrophages, 30 the 2 main polarization-based subtypes have more or less opposite functions in tumor: M1 macrophages are believed to exert anti-tumor effect by promoting the Th1 immune response; M2 macrophages favor the Th2 immune response, which facilitates tumor progression.…”
Section: Discussionmentioning
confidence: 99%